Efficacy of Cannabidiol in Pediatric Patients: Postmarket Experience at a Single Center - Hovey, Sara W.; Jacobson, Jessica L. (Journal of Pediatric Neurology, 2023)
The purpose of this research was to determine the postmarket efficacy and safety of cannabidiol in pediatric patients with Lennox–Gastaut's syndrome (LGS), Dravet's syndrome (DS), and other drug-resistant epilepsy (DRE). This was a single-center, retrospective cohort study in pediatric patients who received prescription cannabidiol at a single center. The primary outcome was the reduction in seizure frequency of all seizure types as measured by the Engel outcome scale at 3 months after initiation of cannabidiol. Thirty-six patients were included. The most common outcome in all three groups was an Engel Class III outcome 3 months following initiation of cannabidiol. Most patients in all groups experienced some clinical benefit and only 33% of patients experienced no clinical benefit. The maximum tolerated dose of cannabidiol at 3 months ranged from 5 to 31 mg/kg/d with a median of 17.9, 13.2, and 18.0 mg/kg/d in the LGS, DS, and DRE (other) groups, respectively. Eight patients discontinued cannabidiol at 3 months and only two patients were hospitalized after initiation of therapy. Seventy-five percent of patients did not report any adverse side effects. Based on the Engel outcome scale utilized within this study, pediatric patients with LGS, DS, and DRE (other) may experience a worthwhile improvement in seizure frequency while on cannabidiol. Further studies are needed to determine the long-term efficacy and safety of cannabidiol and discern predictors of response to therapy.
Keywords: cannabidiol; Dravet's syndrome; drug-resistant epilepsy; Lennox–Gastaut's syndrome; pediatric; seizure